The impact of acute and chronic exercise on thrombosis in cardiovascular disease - Bacon, Simon L.; Pelletier, Roxanne; Lavoie, Kim L. (Thrombosis and Haemostasis, 2009)
There is now a large and impressive literature showing that people who engage in chronic aerobic exercise or who have better cardiovascular fitness levels, tend to live longer and have lower levels of cardiovascular disease (CVD). However, there is a paradox, as acute aerobic exercise has been associated with an increased risk of CVD events. There are now a number of review articles suggesting that the differential benefits of chronic, relative to acute, exercise might be due to thrombotic changes, though the majority of this data is derived from healthy individuals. However, acute exercise is of greater concern and chronic exercise of greater benefit to patient populations. In addition, these higher risk groups tend to present with more complex profiles, e.g. they may be taking medications that influence thrombotic pathways. As such, the current review has focused on newer information relating to exercise, physical activity and thrombosis in patient populations, and highlights some of the growing area’s in the field. For example, the impact of warm-up exercise, the interaction of medications, and issues surrounding the optimal volume and intensity of exercise.
Keywords: Exercise; fibrinolysis; coagulation; platelets